Author Correction: The energy cost of polypeptide knot formation and its folding consequences - Andrés Bustamante; Juan Sotelo-Campos; Daniel G. Guerra; Martin Floor; Christian A. M. Wilson; Carlos Bustamante; Mauricio Báez (Nature Communications, 2017)
The original version of this article contained an error in the spelling of the author Christian A.M. Wilson, which was incorrectly given as Christian M.A. Wilson. This has now been corrected in both the PDF and HTML versions of the article.